SURVEI KETERAMPILAN BATTING TIM CRICKET PUTRA KABUPATEN PANDEGLANG PADA PERSIAPAN PORPROV - Aminudin Aminudin; Mastri Juniarto; Mustafa Masyhur (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
This study aims to make the male cricket players of Pandeglang Regency better understand about batting skills so that in the real championship players are even better at doing batting techniques in the game of cricket. This research was conducted in Banten. Data collection was carried out at NETS or the training ground located at the South Tangerang Puspitek, on 14, 16, 19, and 21 July 2022.This research method is descriptive with survey technique. The population in this study were all male cricket players who will compete at the VI 2022 Provincial Sports Week (PORPROV) in Banten. The sample is the men's cricket team of Pandeglang Regency which will compete at the VI 2022 Provincial Sports Week (PORPROV) in Banten. Based on the problems raised and supported by theoretical descriptions and frameworks of thinking and then analyzing the data, the results of the study can be concluded that the overall results of batting skills show 69% success and 31% failure.